The hedonic valuation of South African wine brands - D. Priilaid; P. van Rensburg (South African Journal of Business Management, 2012)
Working with a set of 35 South African wine brands identified in Priilaid and Van Rensburg (2010a), this study presents two brand valuation techniques that combine non-ordinal wine valuation models with conventional methods of valuation. The first price-premium approach defines brand equity value as the difference between a wine's price and a valuation of its intrinsic worth. The second quality premium approach defines brand equity value as the difference between a wine's intrinsic value and, instead of price, the value of its perceived quality when sampled sighted. With a set of assumptions regarding consistency in future wine quality, hectorage, price premiums, and sales volumes, brand valuations for each method are calculated as the net present value of the brand premiums paid per unit over the total cases sold. The consequent computations reveal how the price-premium method realises a mean valuation three times greater than the average derived from the alternate quality premium method. This difference is attributed to extreme valuations noted at either end of the price-premium sample, and suggests that this method is perhaps less conservative than perceived quality premium-based valuations. Additionally, the specification of perpetuity is observed to be too extreme. Alternate time scenarios are considered, with a period of ten years posited as perhaps more appropriate to such computations.
Keywords: 650